The Role of Social Media as a Public Sphere in the Algerian Protests: An Analytical Study - (:unkn) unknown (Routledge, 2021)
This paper examines the role of social media as a public sphere during the Algerian protests. A survey method was used on a randomly selected sample of social media users in Algeria. Findings showed that social media outlets were an alternative to traditional media, civil societies and opposition political parties. Furthermore, social media played an effective role in pulling people out of the spiral of silence and got them into the spiral of expression by a new perspective of explaining the mechanisms of social media influence in forming public opinion in exceptional circumstances when fear of isolation and conformity were no longer factors. Results also showed that social media expanded political participation and promoted democracy and freedom of expression in Algeria. © 2021 World Communication Association.
Keywords: Algeria; protests; public sphere; Social media